2004
DOI: 10.1080/08870440310001594501
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrepancies and their resolution: quality of life in survivors of childhood cancer

Abstract: Survivors of childhood cancer are at risk of compromised physical and psychological functioning as a result of disease and treatment. However, survivors experiencing similar physical problems vary considerably in their self-reported Quality of Life (QOL) raising questions about the processes underlying adjustment and maintenance of QOL. Seventy seven survivors of either Acute Lymphoblastic Leukaemia (ALL) or tumours of the Central Nervous System (CNS) completed a standardised measure of QOL and semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
3
7
0
2
Order By: Relevance
“…Interestingly, both the survivors and the controls rated their physical health higher than their psychosocial health. Our findings on the physical health aspects of PedsQL TM confirmed the results of some previous studies reporting higher HRQL with generic instruments for the survivors of childhood cancer than healthy controls [16,23]. Shankar estimated with Health Utilities Index system overall HRQL scores lower than general population [33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, both the survivors and the controls rated their physical health higher than their psychosocial health. Our findings on the physical health aspects of PedsQL TM confirmed the results of some previous studies reporting higher HRQL with generic instruments for the survivors of childhood cancer than healthy controls [16,23]. Shankar estimated with Health Utilities Index system overall HRQL scores lower than general population [33].…”
Section: Discussionsupporting
confidence: 93%
“…Some publications report that adult childhood cancer survivors have positive attitude to their life situation despite or as a result of their cancer experience [3], and others show that survivors are at a greater risk for multiple problems [10,[16][17][18] than their age-mates. The findings regarding the determinants of HRQL for childhood cancer survivors are ambiguous [19].…”
Section: Introductionmentioning
confidence: 98%
“…These findings are consistent with previous reports of pediatric brain tumor survivors' difficulties with social functioning when compared with multiple groups including classmates (Barrera et al, 2005;Chen, Chen, & Haase, 2008; Gerhardt et al, 2008;Vannatta et al, 1998), healthy peers (Palmer, Meeske, Katz, Burwinkle, & Varni, 2007), and other illness control groups (Bonner et al, 2008), including other cancers (Eiser, Greco, Vance, Horne, & Glaser, 2004;Zebrack & Chesler, 2002). Our findings are also consistent with a recent investigation of factors influencing depressive symptoms in survivors, whereby global self-worth predicted survivors' self-reported depressive symptoms (Barrera, Schulte, & Spiegler, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…This resulted in detailed information about the kind of difficulties patients experienced but did prevent us from comparing absolute QOL scores with previously published work. It has previously been shown that QOL of patients with cancer [15] and their mothers [16] is substantially below that expected from population norms based on standardized measures. In the future it would be important to determine any relationship between discrepancies, strategies and quality of life, but such an analysis is dependent on larger samples.…”
Section: Discussionmentioning
confidence: 99%